Partnering parasites: evidence of synergism between heavy Schistosoma haematobium and Plasmodium species infections in Kenyan children. - Lia S Florey; Charles H King; Melissa K Van Dyke; Eric M Muchiri; Peter L Mungai; Peter A Zimmerman; Mark L Wilson (Public Library of Science (PLoS), 2012)
BACKGROUND:Residents of resource-poor tropical countries carry heavy burdens of concurrent parasitic infections, leading to high rates of morbidity and mortality. This study was undertaken to help identify the social and environmental determinants of multiple parasite infection in one such community. METHODOLOGY/PRINCIPAL FINDINGS:Residents of Kingwede, Kenya aged 8 years and older were tested for presence and intensity of S. haematobium and Plasmodium spp. infections in a cross-sectional, household-based, community survey. Using General Estimating Equation (GEE) models, social and environmental determinants associated with patterns of co-infection were identified, with age being one of the most important factors. Children had 9.3 times the odds of co-infection compared to adults (95%CI=5.3-16.3). Even after controlling for age, socio-economic position, and other correlates of co-infection, intense concomitant infections with the two parasites were found to cluster in a subset of individuals: the odds of heavy vs. light S. haematobium infection increased with increasing Plasmodium infection intensity suggesting the importance of unmeasured biological factors in determining intensity of co-infection. CONCLUSIONS/SIGNIFICANCE:Children in this community are more likely to be infected with multiple parasites than are adults and should therefore be targeted for prevention and control interventions. More importantly, heavy infections with multiple parasite species appear to cluster within a subset of individuals. Further studies focusing on these most vulnerable people are warranted.